Agenda 2020 and the Olympic movement - MacAloon, J. J. (Sport in Society: Cultures, Commerce, Media, Politics, 2016)
This paper examines the current Olympic bidding crisis and evaluates the accompanying Agenda 2020 reform process at the International Olympic Committee. The organization`s decline in public opinion, particularly in Europe, is associated with its recent failure to consistently and convincingly represent the Olympic Movement (as opposed to the Olympic Sport Industry). Using IOC relations with international human rights organizations as a template, real progress in the course of the Agenda 2020 process was achieved, but then suspended or reversed by the selection of Beijing as host of the 2022 Winter Olympic Games.